The subterranean war on science?: a comment - Pearce, Warren (University of Nottingham, 2013)
Last week saw the publication of an article entitled “The Subterranean War on Science” in the Association of Psychological Science’s Observer magazine. The authors – scientists from a range of disciplines – reflect on their experiences of their work becoming noticed in public. In particular, they argue that the harassment, bullying and abuse of scientists constitute a ‘war on science’ which should be publicised, with a view to “enable lawmakers to improve the balance between academic freedom and confidentiality of peer review on the one hand, and the public’s right to access information on the other”.